Analisis Estimasi Cadangan Karbon dari Perubahan Tutupan Lahan di Kota Bengkulu Berbasis Remote Sensing - Yurike Yurike; Wiryono; Essy Agnesta Asdami; Yudha Saktian Syafruddin; Person Pesona Renta (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Land cover changes in Bengkulu City have significant impacts on carbon stock dynamics, which play a vital role in climate change mitigation. This study aims to analyze carbon stock estimates resulting from land cover changes using remote sensing technology. Landsat and Sentinel-2 satellite imagery data were used to map land cover changes over a specific period, employing a supervised learning-based classification method. Further analysis was conducted to estimate carbon stocks using calculations from the ICLEI Calculator approach. The results of the study indicate a decrease in natural land areas, such as shrubland and mixed dryland agriculture, which declined by 4,236.5 hectares and 3,002.6 hectares, respectively. The conversion of these lands into settlements, plantations, and paddy fields led to a significant decrease in total carbon stocks from 340,095.55 tons in 2014 to 279,033.7 tons in 2024. Additionally, the spatial distribution of carbon stocks in the study area showed patterns correlating with anthropogenic pressures and urban spatial planning policies. The main factors influencing these changes include urbanization, plantation expansion, and land conversion for economic purposes. This study underscores the importance of sustainable land management to prevent ecosystem degradation and support carbon stock enhancement. Conservation efforts, ecosystem rehabilitation, and prudent land-use policies are strategic steps in maintaining carbon balance and mitigating the impacts of climate change.